Effect of pulmonary rehabilitation on functional exercise capacity and hypoxemia in patients with interstitial lung diseases: a retrospective study - Fuschillo, Salvatore; De Felice, Alberto; Elia, Andrea; Martucci, Michele; Gaudiosi, Carlo; Vitale, Dino; Maniscalco, Mauro (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Introduction: Interstitial lung diseases (ILDs) are a heterogeneous group of lung disorders characterized by dyspnea on exertion, exercise-induced hypoxemia and reduced exercise tolerance. There are some evidences that pulmonary rehabilitation (PR) successfully treats these manifestations. Objective: To identify if pulmonary rehabilitation can achieve a clinically significant improvement of functional exercise capacity measured by 6-minute walk test (6-MWT) and arterial blood gases analysis (ABG) in patients with ILDs. Methods: A retrospective secondary analysis of the patients’ records from in-patients of a pulmonary rehabilitation center between 2012 and 2015. Profiles of 38 patients who had completed 4-6 PR weeks were included. 6-MWT distance, dyspnea and fatigue Borg score and ABG at baseline and the end of the pulmonary rehabilitation were compared. Results: There was a statistically and clinically significant improvement in 6-MWT distance after PR with a mean difference for change in distance walked of 68.5±54.2 m. The pre post PR variation of dyspnea and fatigue Borg score significantly improved (-2.3±3.7, and -1.7±2.9, always p≤0.001). Among the ABG parameters, only the resting PaO2 showed a significant improvement after PR (Delta PaO2= 4.6±8.5 mmHg, p=0.005). Conclusions: A 4-6 week of PR improves functional exercise capacity and hypoxemia in patients with ILDs.